Distribution and assessment of heavy metal in sediments of Malacca Strait. (May 2022) - Zhang, Hui; Liu, Shengfa; Ai, Lina; Cao, Peng; Wu, Kaikai; Cui, Jingjing; Wang, Hongmin; Mohamed, Che Abd Rahim; Shi, Xuefa
Abstract: In this study, we explored the heavy metal elements in 42 surface sediments from the Malacca Strait in terms of distribution, controlling factors, environmental quality, and primary sources. An analysis of grain size revealed finer sediments near the coast of Malaysia, which gradually thickened toward offshore. In addition, heavy metal elements were abundantly distributed near the coastal area of Malaysia, with a gradual decrease toward the sea; their content increased within waters close to the Perak estuary. Source analysis of heavy metals showed that Cr, Hg, Zn, Cd, and Cu were mostly derived from natural weathering, and their distribution was significantly influenced by sediment grain size. As and Pb were affected by human activities. The environmental quality assessment results showed that Cu, Cr, Cd, and Zn in our study regions were pollution-free. Pb elements showed low-to-moderate pollution, and Hg showed a certain degree of ecological risk due to its high toxicity coefficient. The content of As elements in surface sediments increased significantly when compared to the background value, with several evaluation methods indicating a high-risk index. According to these findings, the area near the mouth of the Perak River is the most polluted, followed by the surrounding coastal areas. Highlights: Cu, Cr, Cd, Zn were pollution-free, Pb showed low-to-moderate pollution. Hg showed a certain degree of ecological risk due to its high toxicity coefficient. As element within surface sediments showed a high-risk index. The Perak River mouth is most polluted, followed by the surrounding coastal areas.